The Political History of Indian Languages: Evolution, Identity and Nation-Building - Pooja S. Khanappagol (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
India’s linguistic landscape, encompassing over 1,600 languages and dialects, has profoundly shaped its political trajectory from ancient times through colonial rule and into the post-independence era. This paper explores the evolution of Indian languages as instruments of identity formation and nation-building, highlighting how linguistic diversity both unified and fragmented the nation. Ancient scriptures like the Vedas established Sanskrit as a unifying elite language, while vernaculars such as Tamil and Prakrit fostered regional identities amid empire-building under the Mauryas and Guptas. Colonial policies exacerbated divisions by promoting English and codifying regional tongues, sparking resistance that intertwined language with anti-imperial nationalism. Post-1947, the challenge of nation-building intensified debates over a national language, pitting Hindi proponents against non-Hindi regions fearful of cultural erasure. The States Reorganisation Act of 1956 redrew boundaries along linguistic lines, affirming language as a core political identity marker and birthing regional parties like the Dravidian movement in Tamil Nadu. Anti-Hindi agitations in the 1960s forced constitutional compromises, retaining English as an associate language and embedding the Three-Language Formula in education policy, though implementation remains contested. This interplay reveals language politics as a double-edged sword: empowering subnational identities while straining national cohesion. Contemporary issues, including the Eighth Schedule’s 22 scheduled languages and demands for inclusion of others like Bhojpuri, underscore ongoing tensions between federalism and unity. Drawing on historical precedents and policy analyses, the paper argues that India’s multilingualism has fortified democratic pluralism but demands adaptive governance to mitigate exclusionary risks. Ultimately, language policy must evolve to embrace hybrids blending English, Hindi, and regionals for inclusive nation-building in a globalized world.